2006
DOI: 10.3917/ctf.037.0157
|View full text |Cite
|
Sign up to set email alerts
|

Adoption et construction identitaire

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…During adolescence, the degree of opposition and conflict between teenagers and their parents was lower than in the previous stage. This is partially related to the fact that teenagers have a deeper understanding of their adoptive status and begin to recognize the humanitarian value of adoption (Brodzinsky, 2011), leading them to develop feelings of “debt” (Rosenfeld et al, 2006, p. 160), as well as a sense of gratitude and loyalty toward their adoptive parents for having raised them. These positive feelings help adoptees to deal with the challenges connected to their minority status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During adolescence, the degree of opposition and conflict between teenagers and their parents was lower than in the previous stage. This is partially related to the fact that teenagers have a deeper understanding of their adoptive status and begin to recognize the humanitarian value of adoption (Brodzinsky, 2011), leading them to develop feelings of “debt” (Rosenfeld et al, 2006, p. 160), as well as a sense of gratitude and loyalty toward their adoptive parents for having raised them. These positive feelings help adoptees to deal with the challenges connected to their minority status.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, curiosity about origins is often very strong during this time and leads to thoughts and even plans for searching for the birth family (Grotevant & Von Korff, 2011; Pinderhughes & Brodzinsky, 2019). A typical challenge consists in finding a healthy balance between the “debt” toward their birth parents who gave them life, and the “debt” toward their adoptive parents who provided love and care (Rosenfeld, Burton, De Coster, & Duret, 2006, p.160).…”
Section: Identity-related Issues In Adopted Youth During the Developi...mentioning
confidence: 99%
“…Parents in non‐integrative position, however, considered only the adoptive family and appeared in denial of the birth parents' psychological presence, displaying signs of anxiety about the topic. Likewise, a qualitative study of four different‐gender couples in Belgium revealed two ways in which adoptive parents managed their child's double family connection (Rosenfeld et al, 2006). By using “superpositioning,” the adoptive parents added birth and adoptive family systems together to create a new coherent system spanning both.…”
Section: Attitudes Toward Children's Birth Parents Among Different‐ge...mentioning
confidence: 99%